SOCIOECONOMIC DETERMINANTS AND SPATIAL ANALYSIS OF ISCHEMIC HEART DISEASE MORTALITY RATE IN FOZ DO IGUAÇU, PARANA, IN 2010 (Fiep Bulletin - online, 2017)
Ischemic heart disease (IHD) are among the leading causes of death in the world and Brazil is one of the developingcountries where occurs more deaths from this cause. Studies indicate that socioeconomic features are related to incidence ofIHD. This study aimed to analyze the spatial distribution of cases of death from IHD that occurred in 2010 in the city of Foz doIguaçu-PR, correlating it with variables related to income and literacy. This is an ecological study, based on analysis of secondaryand retrospective data where the units were its 320 urban census sectors. The analysis demonstrated that the specific mortalityrate (SMR) ranged from 0 to >258 deaths per 100,000 inhabitants. The Moran Global analysis identified significant positivespatial autocorrelation of the census sectors according to SMR by IHD, meaning that census sectors with high and low SMR werenot randomly distributed. There was a significant positive correlation of variables 'literacy of responsible' and 'per capita incomeby household' (progressively from 1 to 10 minimum wages). For the variable 'per capita income from ½ to 1 minimum wages'there was no significant correlation. It is concluded that there are census sectors with high SMR by IHD in Foz do Iguaçu,especially in Northern, East and West districts of the city and were primarily related to the medium and higher income populationand higher literacy rates, consisting of regions and populations where educational measures of health promotion and lifestylechange incentives, such as physical exercise, should be encouraged aiming at preventing IHD.
Keywords: Geographic mapping; heart diseases; border areas